Prevalence of Epstein-Barr virus antibodies in healthy children and adolescents in Vitória, State of Espírito Santo, Brazil - Figueira-Silva,Cecília M. (2004)
The prevalence and age distribution of Epstein-Barr virus infection varies in different populations and there is little information about the epidemiology of this infection in Brazil. We studied the prevalence of EBV antibodies in a sample of 283 children and adolescents between 1 and 21 years old. The sample was taken from two neighborhoods in Vitória (capital city of Espirito Santo, Brazil). The São Pedro (SP) neighborhood represented an area with lower socioeconomic status and the Praias (P) neighborhood represented an area with higher SES. Anti-VCA (Virus Capsid Antigen) antibodies were detected by ELISA and anti-EBNA (Epstein-Barr Nuclear Antigen) antibodies were detected by an anti-complement immunofluorescence method, both using commercial kits. The results showed an overall prevalence rates of anti-VCA and anti-EBNA of 71% and 54% respectively. The prevalence for both anti-EBV antibodies was higher and probably the infection occurred earlier in the SP neighborhood. Among the various socioeconomic factors studied only low family income and maternal education level were significantly correlated with a higher frequency of positive serology for anti-VCA. These results demonstrate that there is a high prevalence of EBV antibodies in children and adolescents living in Vitória, that occurs more frequently at a younger age in children from families with low socioeconomic status. In addition, the results demonstrate an intermediate age distribution pattern between those reported in developed and underdeveloped countries.